Teacher’s Challenges and Strategies in Teaching English in Rural Areas - Saputri, Yasinta Eka; Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the challenges and strategies employed by English teachers in rural junior high schools in Tanjung Jabung Timur, Indonesia, particularly in the context of the Merdeka Curriculum. As English becomes increasingly important as a global lingua franca, its role as a foreign language (EFL) in Indonesia's education system is crucial. The research utilized a qualitative, phenomenological design, focusing on three schools: SMPN 9 Tanjung Jabung Timur, SMPN 2 Tanjung Jabung Timur, and MTsN 02 Tanjung Jabung Timur. Researchers collected data through classroom observations and in-depth interviews with English teachers, ensuring data reliability using trustworthiness techniques. Researchers used the Miles and Huberman approach for data analysis, uncovering patterns and strategies employed by teachers in rural settings. Professional development remains a significant challenge, with formal training opportunities being scarce. Teachers often use self-directed learning, informal networks, and online resources to meet professional demands. The study calls for more targeted interventions to support rural teachers, foster greater parental involvement, and improve educational infrastructure. Recommendations emphasize reducing disparities between rural and urban education to create a more inclusive and equitable system in Indonesia